Zoom Cloud Meeting and Tutor Performance In Online Japanese Language Learning: A Qualitative Study At Sakura Fubuki - Fajriyan Megawati Azani; Ria Yulia Gloria; Iis Arifudin (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study employed a qualitative descriptive approach to examine the utilization of Zoom Cloud Meeting as a supporting medium for tutor performance in online learning at the Sakura Fubuki Online Japanese Language Course Institution. Data were collected through observations, interviews, and documentation studies and analyzed using the Miles and Huberman (1994) interactive model. The findings reveal that Zoom Cloud Meeting supports tutor performance through effective planning, implementation, and evaluation of online learning activities. Tutors utilized various Zoom features, such as screen sharing, breakout rooms, chat, and recording functions, to facilitate interactive Japanese language learning. Regular evaluations also contributed to identifying challenges and improving instructional practices. The use of Zoom enhanced learning effectiveness, strengthened communication, and expanded access to Japanese language education regardless of geographical limitations. However, several challenges remained, including unstable internet connections, technical issues, and varying levels of student participation. In conclusion, Zoom Cloud Meeting has been effectively utilized as a learning platform that supports tutor performance and contributes to the successful implementation of online Japanese language instruction at the institution.